THE EFFECT OF PRODUCT DESIGN, PRICE AND LOCATION TOWARD PURCHASE DECISION STUDY OF BUKIT MUTIARA JAYA SEMARANG - Dani Suprianto; Hari Susanta Nugraha; Sendhang Nurseto (Universitas Diponegoro, 2014)
Purchasing behavior approach, Shoham and Dalakas said physical factors can influence costumer purchases. This study establishes the design of the product, the price and location as the house base purchasing decisions. This means the product design factors, the price, and the location is the basis of consumer consideration before deciding to buy a house in a residential Bukit Mutiara Jaya Semarang. This type of research is explanatory research, by using a self questionnaire administrator as the data research. The tools used are interviews and questionnaires. The population in this study are those who buy and simultaneously inhabit a residential home in Bukit Mutiara Jaya Semarang. Calculation of the sample using non-probability sampling technique, the type used is purposive sampling with respondents 86 people. Analysis of the data used is linear regression analysis. The conclusion from this study is that there is influence between product design, price and location of the house buying decisions in the Bukit Mutiara Jaya Semarang. Product design influence by 18,9%, price by 25,4% and location by 18%. Jointly influence the design of the product, the price and the location of 28% while 72% is influenced by other factors. Advice: the company must conduct periodic evaluation and improvement of the design of the product to be made so that a better product in the eyes of the consumer, the price set by the developer to be more attractive and viable for the consumer as well as the location of housing that must be considered by both the developer of the facilities and infrastructure, access, as well as the need for clean water is a strategic location in order to be trusted by consumers.